MOTIVASI IBU RUMAH TANGGA DALAM MEMBELAJARKAN ANAK USIA SEKOLAH DI PARAMAN AMPALU KENAGARIAN RABI JONGGOR KABUPATEN PASAMAN BARAT - Dayanthy, Fitri; Rianto, Slamet; Keslan, Widya Prari (Pendidikan Geografi, 2013)
This research is aimed to obtain the data, process, analyze and discuss the data about mother`s motivation in teaching their children at the school-age at Paraman Ampalu Kenagarian Rabi Jonggor Pasaman Barat. Type of this research was all mothers who have the children at school-age at Paraman Ampalu Kenagarian Rabi Jonggor Pasaman Barat. The sample of this study was taken by using random sampling technique where 20 % of the sample consisted of 68 people. The instrumend used was questionnaire. The data was analyzed by using percentace formula. The result of this research found: 1) The level of mother`s education of Paraman Ampalu Kenagarian Jonngor who graduated SD (35,29%), it praved the mother`s education of the reserch`s resuls was good. 2) The mothers have the time for teaching their children about 1-2 hours with the persentace (54,41%), it proved that the time which was had by the mother in teaching their cildren was good. 3) The mother`s experience which is gotten from the school in teaching their children about (38,24%), it proved that the mother`s experience was good. 4) Mother`s backgroud knowledge in teaching in teaching their children was good enough but (47,065%) was still not good, there fore the mothers asked their children to study in groups.